Relationship between knee extensor moment arm and long-sprint performance in male 400-m sprinters - Tomita, D.; Suga, T.; Ueno, H.; Miyake, Y.; Otsuka, M.; Terada, M.; Nagano, A.; Isaka, T. (Translational Sports Medicine, 2018)
The magnitude of the knee extensor moment arm (MA) may be a key morphological factor in achieving superior 100-m sprint performance, potentially by enhancing maximal sprint velocity in sprinters. To further understand the advantage of a greater knee extensor MA in athletic events, we examined the relationship between knee extensor MA and long-sprint performance in well-trained 400-m specialized sprinters. Twenty-eight male 400-m sprinters and 28 physical size-matched male non-sprinters participated in this study. Quadriceps femoris size, evaluated by anatomic cross-sectional area (ACSA) and muscle volume (MV), and knee extensor MA were measured in participants using magnetic resonance imaging. The quadriceps femoris ACSA and MV, and knee extensor MA did not differ significantly between sprinters and non-sprinters. In sprinters, quadriceps femoris MV, but not ACSA, and knee extensor MA were significantly correlated with their 400-m personal best times. After adjusting for body height and/or body weight, it was found that significance remained only for knee extensor MA. These present findings suggest that in addition to 100-m sprinting, the magnitude of knee extensor MA may be a key morphological factor in achieving superior long-sprint performance in well-trained 400-m specialized sprinters.